Karakteristik Historiografi Sirah Nabawiyyah Muhammad Quraish Shihab - Rofiq, Ahmad Choirul; Ajhuri, Kayyis Fithri; Qohar, Abd. (Universitas Islam Negeri Raden Intan Lampung, 2020)
Sirah Nabawiyyah has an important position in the viewpoint of Indonesian Muslim scholars, unfortunately specific works of the Prophet biography are rarely found in Indonesia. As a well-known interpreter of the Qur'an, M. Quraish Shihab has a historiographical work entitled Membaca Sirah Nabi Muhammad Saw dalam Sorotan al-Qur’an dan Hadis-Hadis Shahih that discusses critically about the figure of the Prophet. This library research with historical method analyzes the background of writing, sources of writing, and historical explanations contained in his work. Finally it was concluded that the book was written in accordance with the need of Indonesian Muslims to discuss the history of the Prophet Muhammad critically. The references consist of the Qur'an, the Prophet traditions, the books of Sirah Nabawiyyah, and other relevant books. Because it was written by a commentator of the Qur'an, the verses of the Qur'an are not only quoted with textual translations, but are accompanied by in-depth explanations so that its historical explanations are almost similar to interpretations of the Qur'an. It is able to explain in detail the life of the Prophet with critical analysis and illustrative pictures. In addition, its explanations greatly emphasize the humanity of the Holy Prophet. Therefore this work is not excessive in displaying the Prophet miracles or extraordinary things.